Examining vocational college student learning needs toward entrepreneurship courses in Southwestern China - Xiaoqing Wang; Thanin Ratanaolarn; Jirarat Sitthiworachart; Jianming Cui (Edelweiss Applied Science and Technology, 2025)
The present research aimed to study the student learning needs assessments of entrepreneurship courses in vocational colleges of southwestern China to identify students' learning needs based on the perspectives of creativity, openness to experience, project-based blended learning, design thinking, and entrepreneurship courses. The researcher employed a multi-stage sampling method to select a sample size of 400 current vocational students from four regions in southwestern China to participate in this research. The collected data were analyzed using descriptive statistics to determine the means of 15 items. The results showed that the mean values of the items ranged from 3.66 to 4.28, and all items reached at least the need level. Furthermore, respondents strongly agreed on the importance of enhancing openness to experiences and creativity in entrepreneurship courses. Meanwhile, the respondents also indicated the need for project-based blended learning and design thinking as the learning methods to be used in the teaching practices of entrepreneurship. The results of this study are expected to benefit educators in the process of developing new teaching methods and curricula in the field of entrepreneurship education.
Keywords: Higher Education and Employability; Entrepreneurship Studies and Influences; Higher Education Learning Practices